Use of the Computer and Internet by Teachers in Medical Education: A Study at Medical Colleges of Pakistan - Muhammad Muizz Hassan, Sobia Aamir, Naushabah Malik, Nadeem Naeem, Muhammad Abdullah Avais, Gul Muhammad Shaikh, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and aim: In recent decades, formal medical education has evolved considerably, especially since computers and the Internet were introduced. A major part of the medical curriculum in most industrialized nations is the study of information technology (IT). During formal classroom teaching at the undergraduate level, the present study examined the methods of teaching, the extent of using computers, and the use of Internet by teachers. Methods: A questionnaire based study was carried out on 126 medical teachers in medical colleges of Pakistan from October 2021 March 2022. Assisting professors, associate professors, and professors are the faculty members involved in the study. Study participants did not include tutors, demonstrators, or residents. Prior to study conduction, ethical approval was taken. Additionally, the questionnaire asked questions regarding the use of computers and the internet in teaching, in addition to the basic information, such as gender, age, designation and department. We pretested it with a randomly selected group of teachers and based on their feedback, we made some minor modifications and deleted some questions. Results: Of the total teachers participating, there were 90 (71.4%) male and 36 (28.6%) females. Participants were distributed based on their age as follows: 78 (61.9%) <35 years, 13 (8.1%) 36-50 years, and 35 (27.8%) >50 years. The incidence of traditional teaching, computerized projections, teaching through slides, and combination of traditional methods with slides were 19 (15.1%), 107 (84.9%), 68 (54%), and 32 (25.4%) respectively. Based on pattern of internet usage for teaching, the occurrence of collection of teaching materials without internet, collection of teaching materials using internet, access from desktop, and access from smartphones were 28 (22.2%), 88 (69.8%), 66 (52.4%), and 16 (12.7%) respectively. A significant statistical correlation exists between computer and Internet use among teachers of younger ages, with more frequent usage among teachers of younger ages. Conclusion: The present study concluded that Medical education has become increasingly computer-based and Internet-based. Furthermore, its use is more common among younger professors. However, the most noteworthy conclusion was that the majority students still choose chalkboard lecturing for better knowledge of the material. Keywords: Medical education, Computer, Internet